Long waves and short cycles in a model of endogenous financial fragility - Soon Ryoo (University of Massachusetts, Department of Economics, 2009)
This paper presents a stock-flow consistent macroeconomic model in which financial fragility in firm and household sectors evolves endogenously through the interaction between real and financial sectors. Changes in firms' and households' financial practices produce long waves. The Hopf bifurcation theorem is applied to clarify the conditions for the existence of limit cycles, and simulations illustrate stable limit cycles. The long waves are characterized by periodic economic crises following long expansions. Short cycles, generated by the interaction between effective demand and labor market dynamics, fluctuate around the long waves.
Keywords: E12; E32; E44; 330; cycles; long waves; financial fragility; stock-flow consistency; Lange Wellen; Konjunkturtheorie; Finanzsektor; Finanzmarktkrise; Theorie